The Federal Democratic Republic of Ethiopia : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for The Federal Democratic Republic of Ethiopia. (IMF Staff Country Reports; Country Report ;, 2018)
Context: In 2017/18 growth slowed due to political uncertainty and appropriately restrictive macroeconomic policies. The external current account deficit narrowed to 6.4 percent of GDP reflecting public-sector fiscal consolidation and a tight monetary policy stance. Reserves were thin and foreign exchange shortages persisted. Prime Minister (PM) Abiy Ahmed took office in April 2018, catalyzing a drive for reforms, including towards economic opening. Outlook: Output growth is expected to accelerate to 8.5 percent in 2018/19 as political uncertainty abates and financial inflows temporarily ease external constraints. The Debt Sustainability Analysis (DSA) continues to assess Ethiopia at high risk of debt distress. Reforms announced by the authorities-including privatizations and opening key sectors to competition and private investment-pose a substantial upside growth potential.